INSTITUTIONALIZATION OF REGIONAL POLITICAL ELITES IN THE PROCESS OF RUSSIAN NATIONAL INTERESTS IMPLEMENTATION: GENERALIZATION OF SOME FINDINGS OF THE STUDY - M. A. Kazakov (Вестник Кемеровского государственного университета, 2015)
The paper provides some generalizations about the findings of the research supervised by the author presented to the scientific and expert community to discuss the use and further study of the phenomenon in order to optimize practices and processes that are strategically important for the country’s political development.